Tuberculous otitis media: a resurgence?. Issue 9 (20th July 2017) - Kameswaran, M; Natarajan, K; Parthiban, M; Krishnan, P V; Raghunandhan, S
Abstract: Objective: Tuberculosis is a global health problem that is especially prevalent in developing countries such as India. Recently, atypical presentation has become more common and a high index of suspicion is essential. This study analysed the various presenting symptoms and signs of tuberculous otitis media and the role of diagnostic tests, with the aim of formulating criteria for the diagnosis. Methods: A total of 502 patients underwent tympanomastoidectomy over a two-year period. Microbiological and histopathological examinations and polymerase chain reaction analysis of tissue taken during tympanomastoidectomy were performed. Results: A total of 25 patients (5 per cent) were diagnosed with tuberculous otitis media. Severe mixed hearing loss, facial palsy, labyrinthine fistula, post-aural fistula, perichondritis and extradural abscess were noted. Conclusion: There seems to be a resurgence in tuberculous otitis media in India. Microbiological, histopathological and polymerase chain reaction tests for tuberculosis are helpful for its diagnosis.